a) x^2 – 2xy + y^2 – 2021x + 2021y b) 3x(x+2) – 3x^2 = 18

a) x^2 – 2xy + y^2 – 2021x + 2021y
b) 3x(x+2) – 3x^2 = 18

2 bình luận về “a) x^2 – 2xy + y^2 – 2021x + 2021y b) 3x(x+2) – 3x^2 = 18”

  1. a, x² – 2xy + y² – 2021x + 2021y
    = (x-y)² – 2021(x-y)
    = (x-y)(x – y – 2021)
    b, 3x(x+2) – 3x² = 18
    3x² + 6x – 3x² = 18
    6x=18
    x=3

    Trả lời
  2. Giải đáp+Lời giải và giải thích chi tiết:
    a)
    x^2 – 2xy + y^2 – 2021x + 2021y
     =(x-y)^2-2021(x-y)
     =(x-y)(x-y-2021)
    b)
    3x(x+2) – 3x^2 = 18
    =>3x^2+6x-3x^2=18
    =>6x=18
    =>x=18:6
    =>x=3
    Vậy x=3

    Trả lời

Viết một bình luận

Câu hỏi mới